Speak like me: How language shows group identity among teenagers - Fhonna, Rahmi; Rosfita, Rosi (Accentia: Journal of English Language and Education, 2025)
This study investigated how language functioned as a marker of group identity among teenagers in contemporary digital and social environments. While many studies discuss youth language variation, few explore how linguistic choices actively construct social belonging. Using a qualitative research design, semi-structured interviews were conducted with 10 high school students aged 15–18. They were selected through purposive sampling based on their active involvement in peer-group communication as well as active daily users of messaging and social media platforms (like Instagram, Tik Tok, and Facebook). Data were analyzed through thematic analysis to identify patterns in how teenagers used spoken, written, and visual language to signal identity. Findings revealed three major themes: slang and exclusive vocabulary as identity markers; emojis, memes, and reaction symbols as visual identity; and code-switching as social positioning and context shifting. The participants identified specific slang used exclusively within their groups, such as “GWS (get well soon),” which is used sarcastically to tease rather than to express concern; “Gw b aja” (an Indonesian abbreviation meaning “I’m just casual/chill”); “bet” (expressing agreement or acceptance of a challenge); “iykyk” (“if you know, you know”); and “skibidi / rizz / sigma” (TikTok-influenced identity slang). The interviews also revealed that participants strategically used code-switching among Indonesian, English, and local dialects to navigate different social contexts and relational distances. In addition, visual digital language—such as emojis, memes, GIFs, and reaction symbols—functions as a form of “visual identity,” reinforcing a sense of belonging within online interaction spaces. These linguistic practices demonstrate that language among teenagers is not merely a communication tool, but a deliberate process of identity performance, social positioning, and negotiation of membership.